A new species of Decaphora Franganillo, 1931 (Araneae, Sparassidae, Sparianthinae) from Colombia, with an identification key for all known species of the genus - Rheims, Cristina Anne (Zootaxa, 2017)
Sparianthinae Simon, 1897 is a well-characterized subfamily of Sparassidae Bertkau, 1872, with members easily recognized and distinguished from the remaining sparassids by the trilobate membrane with small or inconspicuous median lobe, chelicerae with small retrolateral denticles and male palps bearing a spoon-shaped median apohysis, among others (Jäger 1998; Ramírez 2014). To date the subfamily includes 15 genera of which eight occur in the Neotropical region. Decaphora Franganillo, 1931, Defectrix Petrunkevitch, 1925, Neostasina Rheims & Alayón, 2016, Pseudosparianthis Simon, 1887, Sampaiosia Mello-Leitão, 1930, Sparianthis Simon, 1880 and Uaiuara Rheims, 2013 are exclusively Neotropical (World Spider Catalog 2017). Stasina Simon, 1877 is mostly Oriental, but includes species occurring in the Neotropical region, although their correct affiliation is considered doubtful (Rheims & Alayón, 2016).